2017
DOI: 10.4314/jab.v116i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potentialities and Antiradical Activities of <i>Oxalis corniculata</i> Linn from Tanzania.

Abstract: Introduction:This study provides essential antioxidant potentialities of the plant Oxalis corniculata Linn (creeping wood sorrell) indigenous from Tanzania and the associated precursors of biochemical compounds responsible for its folkloric pharmacological rationales. Methodology and Results: Extracts were made from the whole plant using methanol and ethanol solvents. DPPH assay was used to evaluate its antioxidant potentials while phytochemical screening for precursors of biochemical compounds responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…DPPH test, the ethyl acetate fraction showed the highest free radical scavenging activity, 24.0% with a concentration of 1 mg/mL [19]. The methanol and ethanol extracts of O. corniculata showed significant activity in all antioxidant assays compared to the reference antioxidant ascorbic acid [16].…”
Section: Antioxidantsmentioning
confidence: 89%
See 2 more Smart Citations
“…DPPH test, the ethyl acetate fraction showed the highest free radical scavenging activity, 24.0% with a concentration of 1 mg/mL [19]. The methanol and ethanol extracts of O. corniculata showed significant activity in all antioxidant assays compared to the reference antioxidant ascorbic acid [16].…”
Section: Antioxidantsmentioning
confidence: 89%
“…The search for antioxidant compounds continues to be carried out, especially plants that can be used as food ingredients, including O. corniculata. The O. corniculata can be an important food source of antioxidants with high scavenging ability and rich in biomolecules which are the precursors of most of the biologically active chemicals of medical importance [16].…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al also reported good antioxidant activities of methanol extract and its sub-fractions in various solvents of Oxalis corniculata [27]. Tibuhwa also explored the antioxidant activities and suggested it as the source of side effect-free natural antioxidants which could be the best alternative to synthetic antioxidants in the food processing industry and also possible used in preventive medicine [28]. As antioxidants, flavonoids from these plants provide anti-inflammatory activity [29].…”
Section: Antioxidant Activity Via Dpph Assaymentioning
confidence: 99%